Crisis behind the figures? Belgian trade unions between strength, paralysis and revitalisation - Jean Faniel (Management Revue, 2012)
Unlike most of the trade unions in European countries, Belgian unions managed to preserve a high and stable union density, and strong institutional positions. However, their situation is not blissful and the condition of both the workforce and the unions has been worsening for three decades. This article looks at the strengths and weaknesses of Belgian unions and presents four initiatives of union revitalisation recently developed. The argument is that Belgian unions do not fully size the scope of the difficulties they face. Just like unions in other countries, Belgian unions attempting to develop initiatives of revitalisation have to overcome difficulties to operate their renewal.
Keywords: J51; 650; unions; unions'revitalization; industrial relations; crisis; Belgium